Genetic Disorders Affecting Tubulin Cytoskeleton - Maya Markova; Irina Chakarova; Ralitsa Zhivkova; Venera Nikolova; Valentina Hadzhinesheva; Stefka Delimitreva (Journal of Biomedical & Clinical Research)
The tubulin cytoskeleton is vital for maintenance and dynamics of eukaryotic cells and molecular defects in its components can lead to serious conditions. So far, mutations in genes for alpha-, beta- and gamma-tubulin, motor proteins of the kinesin and dynein family, microtubule-associated and centrosomal proteins have been found to cause disorders in humans. Most phenotypic effects are on the nervous system, leading to abnormal brain development (e.g. lissencephaly and microcephaly) or to neurodegeneration in later life (e.g. amyotrophic lateral sclerosis and frontotemporal dementia). Another group of disorders include the ciliopathies, caused by defects in the axoneme. They include primary ciliary dyskinesia (immotile cilia syndrome), which is characterized by chronic respiratory infections, male infertility and randomly established left-right asymmetry. In most cases, the underlying defects are in axonemal dynein. Mutations in genes for centrosomal components have been shown to cause cortical dysplasia and dwarfism by disrupting the mitotic spindle, and some cases of infertility with maturation arrest are likely to be caused by unidentified mutations damaging the meiotic spindle. In view of these diverse phenotypes, knowledge about mutations affecting tubulin cytoskeleton becomes increasingly useful for clinical practice.